2017 Young Transatlantic Innovation Leader Initiative (YTILI) Fellow - Kassianos, Angelos P. (My University, 2026)
Received the 2017 Young Transatlantic Innovation Leader Initiative (YTILI) Fellow, a programme of the U.S. Department of State in partnership with the German Marshall Fund of the United States (including a 2-week placement at the Centre for Entrepreneurial Innovation at Phoenix, USA: http://blog.ceigateway.com/blog/ytili-pitch-2017
Keywords: Business and industry